LANGUAGE AND BASIC EDUCATION IN INDONESIA - John Bowden, Frederick (Linguistik Indonesia, 2013)
Indonesia is a country with a great richness of local languages spoken within its boundaries – over 700 distinct languages according to Lewis, ed. (2009). Indonesia is also a rapidly developing country with growing incomes and growing educational achievement. Unfortunately, this growth in income and education is unevenly distributed across the country and significant portions of the Indonesian population are missing out on the benefits of increased economic growth and development. To a very large extent, the parts of Indonesia lagging in terms of development are the regions with the richest diversity of languages. In this paper, I argue the case for greater use of local languages in early education in the underdeveloped east of the country, not just as a means of defending local culture but also as a means towards more equitable educational achievement and economic development. I also examine some of the political issues that may be relevant in pursuing greater use of minority languages in classrooms.